Analyzing factors which drives mobile apps users’ intention to purchase paid mobile apps - Dewa, Qidsa Nafis Akal; Astuti, Rifelly Dewi (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: The study is aimed toward understanding the factors that lead to the intention to purchase to a certain paid mobile apps, this objective is influenced by the current phenomenon where there is an increase in mobile apps user spending toward mobile apps and the superb growth of the industry. Method: The research relies on the expectation-confirmation model (ECM) for its research model. It used an online survey to users who already have experience in purchasing mobile apps (N = 276). The research uses structural equation modeling (SEM) with the use of AMOS 24 software to examine the hypothesis. Findings: It is found that confirmation influences perceived value and satisfaction, while the rest of the perceived value, apart from performance value positively affect satisfaction. Then value-for-money value, satisfaction, apps rating, free alternative to the paid apps, and habit have a significant impact on user intention to purchase as only free alternatives to the paid apps have a negative one. Conclusion: The research finding could contribute the finding to understand the mobile apps industry better while for a more practical contribution, there are some suggestions for parties that are related or involved in the mobile apps industry.